Drug-induced dyskinesias, can they be prevented? - Romaniuk Małgorzata (Current Problems of Psychiatry, 2020)
Introduction: Dyskinesia is a symptom complex in the form of involuntary, repetitive movements of lips, lower jaw, tongue, less often the trunk and limbs. Despite the use of newer drugs in treatment neuroleptics, dyskinesia has not ceased to be a clinical problem.